PERENCANAAN DAN UJI PERFORMA ALAT PEMBAKAR SAMPAH ORGANIK - Martana, Budhi; Sulasminingsih, Sri; Lukmana, Muhammad Arifudin (Bina Teknika, 2017)
Garbage is a part that can not be separated from human life, garbage is an item that is wasted or discarded, and is often regarded as something that is not useful. Garbage is also a major problem, especially in big cities. Trash negative impact on the environment, because the waste can lead to environmental pollution, disruption of cleanliness, safety and health. The objectives of this study were (1) identify the state of the art paradigm of organic waste by burning, (2) designing the incinerator simple as one alternative to appropriate technology and is equipped with a system of utilization of the heat produced, (3) gives a solution to the waste problem so it is useful to reduce the waste generated in landfills while, and (4) examine the performance of the incinerator that has been designed. The method of planning the incinerator is divided into (1) the design of the product, (2) the design process, and (3) engineering design, (4) a manufacturing process or manufacture tools, and (5) testing tool. The incinerator is designed in accordance with the planning, the construction of the incinerator is made of a metal plate with a thickness of 3 mm, the dimensions of the combustion chamber is the outer diameter of 350 mm, an inner diameter of 290 mm, and 410 mm high combustion chamber. Organic waste burner is capable of burning organic waste as much as 28 Kg/hour. Garbage burning rate of 9.33 Kg/h, the air discharge design results obtained at 0.0173 m3/sec.